Analysis of scaffolding harmonic excitation - Jarosław Bęc; Ewa Błazik-Borowa; Jacek Szer (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2023)
Scaffolding is equipment usually used at construction sites. A scaffolding structure is lightweight and made of elements used many times. The characteristics of scaffolding make it susceptible to dynamic actions present at the structure or occurring nearby. A scaffolding structure of medium size was subjected to analysis in this paper. The structure FEM model was loaded with single force harmonic excitation with various frequencies ranging from 1 Hz to 12 Hz applied in one of many selected points on the scaffolding façade. In the first step, natural frequencies and mode shapes of the analyzed structure were calculated. Then the full dynamic analysis was carried out to obtain maximum displacements of selected control points. The relation of excitation force frequency and location to the amplitudes of generated displacement was observed. It was found that low excitation frequencies close to the natural frequencies of the structure produced vibrations ranging to large areas of the scaffolding surface. Higher excitation frequencies are usually less propagated at the scaffolding but still may produce some discomfort to the structure users in the vicinity of the excitation force location. Scaffolding is equipment usually used at construction sites. A scaffolding structure is lightweight and made of elements used many times. The characteristics of scaffolding make it susceptible to dynamic actions present at the structure or occurring nearby. A scaffolding structure of medium size was subjected to analysis in this paper. The structure FEM model was loaded with single force harmonic excitation with various frequencies ranging from 1 Hz to 12 Hz applied in one of many selected points on the scaffolding façade. In the first step, natural frequencies and mode shapes of the analyzed structure were calculated. Then the full dynamic analysis was carried out to obtain maximum displacements of selected control points. The relation of excitation force frequency and location to the amplitudes of generated displacement was observed. It was found that low excitation frequencies close to the natural frequencies of the structure produced vibrations ranging to large areas of the scaffolding surface. Higher excitation frequencies are usually less propagated at the scaffolding but still may produce some discomfort to the structure users in the vicinity of the excitation force location.